ANALISIS KINERJA KEUANGAN PADA PT. BANK MANDIRI (PERSERO) TBK - Krisniawati, Krisniawati; Zulkarnain, Muhammad (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2019)
ABSTRACT This research was conducted with the aim to analyze the financial performance of PT. Bank Mandiri (Persero) Tbk ... This study uses secondary data sourced from the website of The Indonesia Capital Market Institute in the form of an annual report of PT. Bank Mandiri (Persero) Tbk in 2011-2015. Data were analyzed using financial performance measurements based on analysis of the Return on Assets (ROA) ratio and the Capital Asset Management Earning Liquidity (CAMEL) ratio consisting of Capital Adequecy Ratio (CAR), Productive Asset Ratio (KAP), Net Profit Margin (NPM) ratio , the ratio of Operating Expenses to Operating Income (BOPO) and Loan to Deposit Ratio (LDR). The results showed that the financial performance based on the ratio of Return on Assets (ROA) at PT. Bank Mandiri (Persero) Tbk is categorized HEALTHY with an average ROA value of 3.46% from the provision of financial performance standards of 1.215%. Based on CAMEL analysis for CAR, KAP, NPM, BOPO, and LDR ratios, the financial performance of the bank is HEALTHY.